Direitos Humanos como disciplina curricular obrigatória - Manzine, Lauzane Puccia (2016)
This study proposes to provide a path through education in order to repair an historical mistake of the Brazilian society and the world. This mistake was formed in the midst of social, racial, sexual and religious prejudices and it still occurs to the present day. The Federal Constitution of 1988 was comprehensive as the binary classification of society which it resulted in a progress for the Human Rights. The United Nations - UN, recently outlined a plan of goals to improve the quality of education called Sustainable Developed Goals - SDGs, which will form the basis for the proposed project that arose, among other reasons, in order to ensure the legacy left by the previous target plan called Millennium Development Goals - MDGs. The purpose of this study is to offer a new school program as a tool to construct the new human being through mandatory lecture of humanities. This new lecture will help to re-educate and replace the social prejudices acquired over the centuries such as humanistic prejudices like, respect, solidarity, equality, fraternity, among others. Furthermore it will help to prepare the new citizens for more participation in social life. Students, especially from high school, were chosen in this study to receive the apprentice of the new lecture of humanities, as it represents the formation of young human being who will be responsible for the decisions in today's world that no longer tolerates: discrimination and inequalities